Health impact assessment of active transportation: A systematic review - Mueller,N; Rojas-Rueda,D; Cole-Hunter,T; de,Nazelle A; Dons,E; Gerike,R; Goetschi,T; Panis,LI; Kahlmeier,S; Nieuwenhuijsen,M (Preventive Medicine, 2015)
ObjectiveWalking and cycling for transportation (i.e. active transportation, AT), provide substantial health benefits from increased physical activity (PA). However, risks of injury from exposure to motorized traffic and their emissions (i.e. air pollution) exist. The objective was to systematically review studies conducting health impact assessment (HIA) of a mode shift to AT on grounds of associated health benefits and risks.MethodsSystematic database searches of MEDLINE, Web of Science and Transportation Research International Documentation were performed by two independent researchers, augmented by bibliographic review, internet searches and expert consultation to identify peer-reviewed studies from inception to December 2014.ResultsThirty studies were included, originating predominantly from Europe, but also the United States, Australia and New Zealand. They compromised of mostly HIA approaches of comparative risk assessment and cost–benefit analysis. Estimated health benefit–risk or benefit–cost ratios of a mode shift to AT ranged between − 2 and 360 (median = 9). Effects of increased PA contributed the most to estimated health benefits, which strongly outweighed detrimental effects of traffic incidents and air pollution exposure on health.ConclusionDespite different HIA methodologies being applied with distinctive assumptions on key parameters, AT can provide substantial net health benefits, irrespective of geographical context.